C shaped canal: Variation and Recommendations - Shrestha, Sushmita; Agrawal, Navin; Vikram, Mannu; Singh, Vimmi; Ayer, Ashok; Rai, Arbind (Journal of College of Medical Sciences-Nepal, 2018)
Root canal morphology is not uniform, variations of root canals are routinely encountered by endodontists making the root canal treatment more challenging. C shaped canal is a variation commonly encountered in mandibular second molars. The main identifying feature of such canals is presence of fins or webs interconnecting with the main canals. Such canal systems require meticulous mechanical and rigorous chemical preparation to ensure desired outcome of the treatment. Proper assessment of tooth morphology, preoperative radiograph along with consideration towards racial predilection will greatly help in accurate identification of such canals pre-operatively. This paper reports a case of C shaped canal in mandibular second molar diagnosed and treated taking all the precautions and adapting necessary modifications in the steps of conventional root canal treatment steps where required thus increasing the likelihood of success.